Experimental Verification of Control Strategies for Satellite Magnetic-Based Attitude Control System Under a Three-Axis Helmholtz Cage Environment - Thanayuth Panyalert; Shariff Manuthasna; Jormpon Chaisakulsurin; Tanawish Masri; Kritsada Palee; Pakawat Prasit; Peerapong Torteeka; Pasu Poonpakdee; Poom Konghuayrob (My University, 2023)
During satellite mission planning and operation, the main function of the satellite's attitude determination and control subsystem (ADCS) is to gather information about the satellite's orientation relative to the inertial reference frame. Additionally, this subsystem generates control actions that produce the required torques for adjusting the satellite's orientation, particularly in the context of the Low-Earth Orbit (LEO) regime. This paper focuses on the satellite three-axis attitude control problem for a de-tumbling mode of spacecraft using only magnetorquers as actuators under the presence of noise and investigates their performance through Hardware-in-the-Loop simulation (HiLs) tests, which consisted of a relative Earth's magnetic field generator along with the SGP-4-based satellite orbital propagator high-level control software. The design, development, and verification of proposed satellite attitude control system (ACS) strategies are presented. In detail, as an example of experimentation, the classical B-dot control algorithm is used for the de-tumbling mode to stabilize and reduce the angular rate, along with the pointing algorithm for orienting the satellite to the desired attitude. Then, a cascade Proportional-Integral-Derivative (PID) is implemented to generate enough torque through the three-axis magnetorquers on the frictionless air-bearing platform to verify the performance of the controller using an onboard computer. Finally, the effectiveness of the co-simulation tested as the primary experiment was confirmed through the integrated simulation process.
Keywords: Inertial Sensor and Navigation; Space Satellite Systems and Control; Spacecraft Design and Technology